Coping and Quality of Life in Patients with Systemic Lupus Erythematosus: A Review - Córdoba Sánchez, Verónica; Limonero García, Joaquín T. (Pensando Psicología, 2015)
Backgorund: Systemic lupus erythematosus (SLE) is characterized by uncertain prognosis, severe symptoms and a negative impact on quality of life (QOL) of patients. Purpose: The aim of this review is to generate a comprehensive approach in order to improve psychological intervention in these patients.Methods: A qualitative review of articles indexed in MEDLINE, PsycINFO and SCOPUS up to July 2015 was conducted. Articles reporting SLE, coping strategies and QOL were included.Results: Twenty-four studies were found, covering different research designs, forms of assessment and intervention. Coping strategies and their relationship with QOL were analyzed in order to describe the best strategies for dealing with SLE.Conclusions: There are no adaptive or maladaptive strategies, and the suitability of these depends on the situation that a patient could sustain; nevertheless, an active coping style seems to help preserve the QOL. The main goal of psychological intervention should be diversify and expand the number of coping strategies used by patients.
Keywords: chronic disease; coping strategies; lupus erythematosus; quality of life; stress; systemic